A coupled system of nonlocal fractional differential equations with coupled and uncoupled slit-strips integral boundary conditions - Ahmad, B.; Ntouyas, S.K. (Нелінійні коливання, 2016)
This paper is concerned with the existence and uniqueness of solutions for a coupled system of fractional differential equations with coupled and uncoupled slit-strips integral boundary conditions. The existence and uniqueness of solutions is established by Banach’s contraction principle, while the existence of solutions is derived by using Leray – Schauder’s alternative. The results are explained with the aid of examples.